Terrestrial self-contained navigation system based on a novel laser Doppler velocimeter. Issue 353 (4th March 2017) - Gao, C.; Wei, G.; Long, X. W.
Abstract : In order to improve the accuracy and manoeuvrability of terrestrial self-contained navigation system, an idea of building an integrated navigation system using a novel laser Doppler velocimeter together with an inertial navigation system is proposed. The structure and performance of the split reuse-type structure of the laser Doppler velocimeter are expounded, and the integrated technology of marching initial alignment and real-time errors compensation are also discussed in detail. The static inertial alignment of the inertial navigation system can be skipped over and the position error of navigation has been decreased from 1180 m in 2 h to 6 m in 2 h. The experiment results show that the strapdown inertial navigation system/laser Doppler velocimeter integrated navigation system can work effectively without parking and the high-accuracy self-contained navigation can be achieved.